Assessment of Material Damage of Boiler Down-Pipes - Krajczyk, A.; Pszonka, A.; Żuchowski, R. (Engineering Transactions, 1991)
The results of damage examination of boiler down-pipes (type OR/32) are presented. The investigation program included: static tension test, determination of fracture toughness, hardness measurement and metallographic examination. It was found that material of worked down-pipes in the vicinity of knees has been damaged and thus these down-pipes must have been removed from service. Taking into account the results of hardness measurement of specimens made of virgin down-pipe knee it has been found that the virgin down-pipes are not fit to be put into service either.